Load-Carrying Mechanism of Post-Tensioned Inter-Module Connections Implemented into Modular Steel Buildings. Issue 4 (12th March 2023) - Shin, Dong-Hyeon; Kim, Hyung-Joon
ABSTRACT: Modular building construction technique is increasingly promoted due to the application of various structural systems and building materials. In order to improve the constructability of inter-module connections in modular buildings, this study aims to develop post-tensioned inter-module connections (PTMCs) which can become an alternative to prevailing inter-module bolted connection details. The PTMCs are experimentally and analytically investigated to ensure that their structural stability and lateral load-carrying capacities are equivalent to those of typical inter-module connections. Evaluation results show that the PTMC specimen possesses similar lateral load resistance with deformation capacity to a specimen employing typical inter-module connection details.